Proximity to Heavy Traffic Roads and Patient Characteristics of Late of Onset Asthma in an Urban Asthma Center - Lin, Ting-Yu; Lin, Horng-Chyuan; Liu, Yun-Sheng; Lo, Yu-Lun; Wang, Chun-Hua; Chang, Po-Jui; Lo, Chun-Yu; Lin, Shu-Min (Frontiers in Medicine, 2021)
Background: Traffic-related pollution is associated with onset of asthma and the development of different phenotypes of asthma. Few studies have investigated the association between traffic proximity and late onset of asthma (LOA) and early onset asthma (EOA). This study was conducted to investigate the associations of LOA phenotypes with a function of the distance between residence and heavy traffic roads (HTRs). Methods: Two hundred and eighty-three patients were (LOA: 78.4%) recruited consecutively from a pay-for-performance asthma program to clarify the patient characteristics and proximity to HTRs within 1,000 m from their residences between EOA and LOA in three urban centers in Taiwan. Subsequent analysis focused on LOA patients (n=210) linking phenotypes and distance to HTRs. Results: Subjects with LOA tended to be older than those with EOA and had shorter asthma duration, poorer lung function, lower atopy, and less exposure to fumes or dust at home. Patients with LOA were more likely than those with EOA to live within 900 m of two or more HTRs (14.3% vs 3.4%, p=0.02). Among LOA patients, minimum distance to an HTR was negatively associated with numbers of specific IgE as well as positively associated with age of onset and body weight significantly. A higher proportion of patients with atopy (26.3 % vs 20.6%, p=0.001. OR: 2.82) and anxiety/depression (21.0% vs 18.1%, p=0.047. OR: 1.81) and a trend of lower proportion of patients with obese (5.7% vs 12.4%, p=0.075) were found to be living within 900 m from HTRs. Conclusions: LOAs tended to live in areas of higher HTR density compared to EOAs. Among LOA patients living close to HTRs, the interaction between traffic-related pollution, allergy sensitization and mood status was the factors associated with asthma onset early. Obese may be the factor for later onset who living far from HTRs.